3-Hydroxy-3-methylglutaryl-coenzyme A reductase modulator: toward age- and sex-personalized medicine. (3rd October 2015) - Pallottini, Valentina
Abstract : Cholesterol homeostasis maintenance is regulated by a cellular feedback system that senses cholesterol amount in cellular membranes. 3-hydroxy 3-methylglutaryl coenzyme A reductase (HMGR) plays a pivotal role in cholesterol metabolism as it is the key rate-limiting enzyme of its biosynthetic pathway; its inhibition provokes a feedback response capable of reducing plasma cholesterol content. HMGR inhibition is a keystone in the treatment and prevention of cardiovascular disease and, therefore, statins (HMGR inhibitors) are widely prescribed even though they may sometimes induce side effects. These drugs are prescribed indifferently to both man and women even if there are several well-known differences in cholesterol metabolism depending on the gender and the age. Thus, gender-related differences in cholesterol metabolism should be taken into account to identify new targets for customized pharmacological treatments for hypercholesterolemia.